Tinjauan Fikih Muamalah Terhadap Praktek Transaksi Menggunakan Koin Di Floating Market Lembang Bandung - Muhamad Hiqal Fahrurrozi; Rizki Rifaldi; Muhammad Fatturachman (JURNAL EKONOMI SYARIAH, 2020)
Now, many people are just only looking for something that is current and unique and ignore the local culture. This is different from the market in Bandung, namely Floating Market Lembang, which uses coins as a medium of exchange in its transactions. This is a new phenomenon in the field of muamalah, so it requires the study of Muamalah Jurisprudence to review its validity. The main problems in this study include: (1) how is the practice of buying and selling with the coin exchange tool in the Floating Market Lembang? (2) what is the view of Jurisprudence regarding the practice of buying and selling with a coin exchange tool. The purpose of this study was to find out about the validity of the practice of buying and selling with a coin exchange tool in the Lembang Floating Market in terms of the study of Muamalah Jurisprudence. The results of this study indicate that the practice of buying and selling with a coin exchange tool is in accordance with Islamic law, which has fulfilled the harmony and its requirements in buying and selling. In addition, the principles of muamalat have been implemented, namely the principle of willingness, does not contain the element of gharar andmaintains sharia maqasid. The legal status of buying and selling in this Floating Market is legal. However, this validity only applies to the Lembang Floating Market and not as a whole for the general public.